Intercultural experience in narrative : expatriate stories from a multicultural workplace - Wilczewski, Michał (Studies in narrative, 2019)
"This book systematically investigates intercultural experiences of Polish managers and specialists delegated by their multinational company (MNC) on an international assignment to China. The book employs narrative inquiry to explore language, intercultural communication, collaboration, learning, and expatriate adjustment in the MNC. This approach offers new insights into intercultural experiences, communication, and cultural challenges faced by an under-researched group of professionals exposed to intensive collaborations with the local managers and employees. The findings also illustrate how the expatriates learned to better navigate the multicultural and multilingual business context and what factors facilitated and inhibited their learning and adjustment. Encouraging the qualitative, context-sensitive examination of expatriate-local personnel interactions, the book will be an invaluable source for scholars and practitioners interested in, among others, novel approaches to investigating language and intercultural communication in international business, cross-cultural management, qualitative cross-cultural research, as well as for lecturers and students interested in Central Europe and China"--